2012
DOI: 10.1108/13683041211276438
|View full text |Cite
|
Sign up to set email alerts
|

Value of information in health services market

Abstract: PurposeThe traditional service market is composed of customers and service providers, interacting within a given structure and following market‐specific rules. These basic attributes are obvious and persistent. The fragile entity, which is essential for normally operating and self‐controlling market, is information. In this context the aim is to distinguish between a background noise, arising from comprehensive marketing campaigns, customer care activities or advertisement and data, advices or knowledge, neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Big data drastically increase business opportunities in commercial, industrial and public sectors (Bititci et al, 2012;Bourne et al, 2018a;Cernohorsky and Voracek, 2012;Davenport et al, 2012;Garcı ´a and Caro, 2009;Rajala et al, 2018). The ability to manage big data is a significant factor in the creation of business value (Davenport, 2006;El Kadiri et al, 2016;Nudurupati et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Big data drastically increase business opportunities in commercial, industrial and public sectors (Bititci et al, 2012;Bourne et al, 2018a;Cernohorsky and Voracek, 2012;Davenport et al, 2012;Garcı ´a and Caro, 2009;Rajala et al, 2018). The ability to manage big data is a significant factor in the creation of business value (Davenport, 2006;El Kadiri et al, 2016;Nudurupati et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Emergency service [111] Supply-demand equation that delivers frontline policing services Air transportation [112] policies and strategies for air transportation (e.g., policies for reducing emissions of commercial aviation Local public policy [113] local public policy process Public sector unit [114] mortality rate of public sector units Concession pricing model [115] determining a rational concession price for highway projects based on pro forma financial statements Highway sustainability [116] highway sustainability based on individual policies with a crucial impact on the success of policymaking Academic performance [117] factors that affect academic performance of migrant student residing in poor migrant neighborhoods Maritime Sustainability [118] integrated sustainability assessment process Information in health care [119] emergent market behaviour enabling evaluation of different public health policies Climate change [120] electricity industry at the same time as addressing climate change issues Participatory urban [121] urban sensing for improving municipality's availability of environmental information at comparable cost level Wireless local area [122] effect of subsidization, revenue sharing, and alliance strategies Airport competitiveness [123] airport investment and city R&D inputs, which support decision-makers on airport competitiveness Electronic health records [124] combination of measures can promote the adoption of electronic health records by different stakeholders…”
Section: Topics and Goods Models And Issues Dealtmentioning
confidence: 99%
“…Natural-societal risk [106] stratospheric ozone to identify points to influence policymakers in addressing risks in a natural system Waste management [107] cost-benefit of construction and demolition waste management practices Strategic conversations [108] soft operational research strategy making an intervention with a top management team Interactive knowledge management [109] knowledge management for improving quality of knowledge in non-hierarchical policy-making groups Waste management [110] economic feasibility of recycling and ratio of savings to costs in construction and demolition waste management Emergency service [111] Supply-demand equation that delivers frontline policing services Air transportation [112] policies and strategies for air transportation (e.g., policies for reducing emissions of commercial aviation Local public policy [113] local public policy process Public sector unit [114] mortality rate of public sector units Concession pricing model [115] determining a rational concession price for highway projects based on pro forma financial statements Highway sustainability [116] highway sustainability based on individual policies with a crucial impact on the success of policymaking Academic performance [117] factors that affect academic performance of migrant student residing in poor migrant neighborhoods Maritime Sustainability [118] integrated sustainability assessment process Information in health care [119] emergent market behaviour enabling evaluation of different public health policies Climate change [120] electricity industry at the same time as addressing climate change issues Participatory urban [121] urban sensing for improving municipality's availability of environmental information at comparable cost level Wireless local area [122] effect of subsidization, revenue sharing, and alliance strategies Airport competitiveness [123] airport investment and city R&D inputs, which support decision-makers on airport competitiveness Electronic health records [124] combination of measures can promote the adoption of electronic health records by different stakeholders Housing market [125] house prices, balances between supply and demand, construction companies' earnings, and vacancy rates Participatory policy [126] participatory procedures to the governance of wider public policy issues Debt accumulation [127] public debt in developing countries and its two-way linkages with economic growth and public f...…”
Section: Topics and Goods Models And Issues Dealtmentioning
confidence: 99%
See 1 more Smart Citation
“…Reference [56] examined in their study, how value co-creation unfolds over time, and identified basic dynamics central to the modeling of service systems. Finally, Reference [57] modeled healthcare services by using agent-based modeling and simulation technique and examined results.…”
Section: Servicesmentioning
confidence: 99%